The level of use of educational applications by teachers of students with intellectual disabilities to support their academic achievement - Alahmari, Abdulaziz Musaed; Al-Qarini, Turki Abdullah (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the level of use of educational applications by teachers of students with intellectual disabilities to support their academic achievement, and the extent of differences between the sample responses according to the variables: (gender, educational qualification, years of experience). The study followed the descriptive approach, and used a questionnaire. It was applied to a random sample (669) of teachers of students with intellectual disabilities In institutes affiliated to the Ministry of Education in Riyadh. The most important results: Teachers "sometimes" use educational applications. There are differences in the level of using educational applications to support students' academic achievement due to the difference in the sample type (in favor of teachers), due to the difference in educational qualifications in favor of those with (other educational qualifications), And due to the difference in the number of years of experience in favor of a sample of experienced (16 years and over). The most important recommendations are: Working to qualify specialists in the field of education for people with intellectual disabilities in universities and colleges on how to employ educational applications in the educational process, which contributes to its practice in the future in reality. Holding training programs and professional development programs for male and female teachers who are working in intellectual education programs and institutes, through which educational applications are introduced and how to benefit from them; to support their students' skills and achieve their goals. Providing tools and equipment related to running and displaying educational applications.
Keywords: Educational Applications; Intellectual Disability; teachers of students with intellectual disabilities